2019
DOI: 10.5604/01.3001.0013.1532
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to pollen allergens in allergic rhinitis expressed by diurnal variation of airborne tree pollen in urban and rural area

Abstract: Exposure to airborne pollen allergens results in allergic symptoms in subjects who are sensitized. The paper presents diurnal variation in the counts of airborne allergenic pollen of selected trees (Betula L., Alnus Mill., Corylus L., Fagus L. and Ulmus L.) in two localities differing in the degree of urbanization: the city of Szczecin (urban) and the village of Gudowo, West Pomerania in northwest Poland (rural) in the years 2012–2014. The measurements were made by the volumetric method using a Burkardtype sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Previous studies showed that airborne pollen loads were low when the amount of precipitation was high ( 47 , 54 ). In concordance with the previous studies, our study found that pollen concentration was negatively correlated with relative humidity and rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that airborne pollen loads were low when the amount of precipitation was high ( 47 , 54 ). In concordance with the previous studies, our study found that pollen concentration was negatively correlated with relative humidity and rainfall.…”
Section: Discussionmentioning
confidence: 99%
“…The release of pollen grains from anthers depends on many factors. Changes in the content of pollen grains in the air are also determined by local habitat conditions and topography [4,9].…”
Section: Discussionmentioning
confidence: 99%
“…The main symptoms of allergy include runny nose, coughing, wheezing, watery eyes, headache, and sinus pain. Currently, the clinical importance of elm pollen in Poland is regarded as low [4], although elm is classified as an important plant allergen elsewhere in the world [5]. Nevertheless, elm pollen allergens are increasingly becoming a cause of allergic reactions also in Poland.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different trends of pollen linked to year [39,40], seasonality [41][42][43], daily [44][45][46], intradiurnal [40,[47][48][49][50][51][52] or hourly variations have been reported [27,53,54], and have to be taken into account for the further distinction between urban or non-urban environments [25,26,52,[55][56][57][58]. In this regard, urban and non-urban components around occupational settings add complexity.…”
Section: Introductionmentioning
confidence: 99%